EVALUATING AND DEVELOPING LOGISTICS SYSTEM FOR EXPORTING SMALL AND MEDIUM ENTERPRISES (CASE STUDY IN YOGYAKARTA PROVINCE AND ADJACENT AREAS, INDONESIA) - Rizkie Syahputera (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2013)
Indonesia is ranked 75 of 155 countries in the world for the Logistics Performance Index. Thus, logistics services efficiency has to be improved to make sure SMEs can be more competitive and gain benefit from international trade arena. Yogyakarta with its viscous culture has become a favorite tourism destination, with many art craft products. Its unique location which far from seaport inflicts higher cost to the exporting cost. The study is to understand the system, understand the constraints and provide recommendation to improve the efficiency of current system.The study uses questionnaire survey as the method to gather the data. It consists of 2 surveys, on survey 1 on SMEs and survey 2 on forwarders. The analysis is mainly descriptive. Results of survey 1 are that the respondents are quite satisfied with current system which is 90% of total respondent, 82 % of total respondents never have problems with the customs, and the biggest problem is uncertain regulation. Results of survey 2 are 89 % of total respondent never have problem with customs, the biggest problem is bribery and uncertain regulations, and the time needed to export is quite long.The recommendations are established by developing 5th party logistics, constructing clear and market responsive regulations, and improving the facilities of transport infrastructure.Keywords: SME, logistics, Indonesia, export.